Ensuring health security for Nigerians by 2050: closing the equity gaps in reproductive health (2019)
Background: Reproductive health is a key foundation for strategies to address health security. It constitutes a vital element in the vision to achieve improved health, quality of life and well-being of individuals and families and the realisation of national economic goals. Developing a blue print for health security in reproductive health matters may contribute to closing the equity gaps in Nigeria by the year 2050. Methods: Gaps in reproductive health were identified through situation analysis of selected reproductive health indices. SWOT analysis was also conducted to outline areas of strengths and opportunities, in addition to weaknesses and threats. Key reproductive health indicators were forecasted for 2050. Results: Despite all efforts, gaps still exist in the country’s reproductive health indices including maternal, perinatal, contraceptive, abortion and gynaecological. Most pregnancy-related deaths are linked largely to preventable causes. If unaddressed, these challenges would undermine gains from previous interventions and responses from governmental and non-governmental organizations and pose serious threats to the nation’s health security. Conclusions: The country must be committed to reproductive health agenda that is focused on the International Conference on Population and Development goal in its bid to achieve health security by the year 2050. Due considerations must be accorded to emerging reproductive health issues like men’s reproductive health and their involvement intheir partners’ reproductive health, and the reproductive health needs of the aged, people with disabilities and those in humanitarian settings. Further in achieving health security for Nigerians by the year 2050, the principles underlying the reproductive health policy of the country must be upheld. These include equity, right based approach, gender and age responsiveness, cultural sensitivity and continuum of care amongst others.